Penerapan Senam Chair Exercise dan Senam Kaki pada Pasien Diabetes Melitus Tipe 2 - Ramadhan, Sahrir; Desty Emilyani; Aan Dwi Sentana (Indonesian Journal Publisher, 2025)
Background: Instability of blood sugar levels (Hyperglycemia) is a condition where there is an increase in blood sugar levels, which can be acute or chronic, due to hereditary factors, obesity, overeating, lack of exercise, and changes in lifestyle. Purpose: Applying Nursing Care to Type 2 Diabetes Mellitus Patients - With Blood Sugar Instability Problems Through the Implementation of Chair Exercises and Foot Exercises. Methods: This research uses a descriptive method with a case study design. The case study subjects were two patients with problems with unstable blood glucose levels. The focus of the case study is nursing care through providing chair exercises and leg exercises, which are carried out for 30 minutes for 3 days. Data collection through interviews, observation and physical examination. Results: In Mrs. N, before being given the chair exercise intervention, the blood sugar level was 328 mg/dl, and for Mrs. S, before being given the leg exercise intervention, the blood sugar level was 199 mg/dl. After implementation for 3 days, Mrs. N's blood sugar level was 244 mg/dl, and Mrs. S's was 181 mg/dl. Conclusion: Chair exercises and leg exercises effectively overcome the problem of unstable blood glucose levels in patients with type 2 diabetes mellitus. Conclusion: Chair exercise and leg exercises effectively overcome the problem of unstable blood glucose levels in patients with type 2 diabetes mellitus. Chair and leg exercises can be used as non-pharmacological therapy to overcome the problem of unstable blood glucose levels.